An Approach Transient Stability Analysis Using Equivalent Impedance Modified in 150 kV South of Sulawesi System - Muhammad Ruswandi Djalal; Herman Nawir; Herlambang Setiadi; Andi Imran (Muhammadiyah University, Sidoarjo, 2017)
One of methods that can be used to determine the stability of a power system if the fault occured is the equal area criterion method. The equal area criterion method (Equal Area Criterion, EAC) is an example of a direct method for predicting the stability and also the critical clearing time (Critical clearing time). However, to calculate the complex calculations required to determine the equivalent impedance of each condition system. In this study used several approaches to facilitate the calculation of the equivalent impedance. This method uses the equation of power losses. This method is equivalent impedance using modified with Ploss and Qloss for Determining Pmax. From the analysis, it can be concluded the use of this method is quite accurate in analyzing or calculating the transient stability of the generator system in South Sulawesi, with each loading condition, before, during and after short circuit. Generator being looked at is Bakaru, Pare, Suppa, Barru and Sengkang.